2021
DOI: 10.1177/00219983211037050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MWCNT addition on the optical band gap of PVA/CS transient biocomposites

Abstract: In recent years, as a result of increasing environmental concerns, biodegradable materials have gained great attention. With the rapid development of electronic technology, the importance of innovation and development of low-cost, sustainable, transient bioelectronics materials is increasing. In this research, the preparation of Poly(Vinyl Alcohol) (PVA), Chitosan (CS), and Multi-Walled Carbon nanotube (MWCNT) biocomposite films have been described. The solution mixing, ultrasonic mixing, and spin coating tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Poly (vinyl alcohol) polymer used in this work has been the subject of several investigations: Choudhary et al 14 reported improved dielectric properties of a polyvinyl alcohol/polyethylene oxide (PVA/PEG) composite upon reinforcement with graphene oxide. Mergen et al 15 developed the optical properties of PVA, Chitosan (CS), and Multi-Walled Carbon nanotube (MWCNT) biocomposite films. Abdallh et al 16 improve that the optical band gap and optical activation energy have been investigated for pure and doped PVA films with different cupper chloride concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Poly (vinyl alcohol) polymer used in this work has been the subject of several investigations: Choudhary et al 14 reported improved dielectric properties of a polyvinyl alcohol/polyethylene oxide (PVA/PEG) composite upon reinforcement with graphene oxide. Mergen et al 15 developed the optical properties of PVA, Chitosan (CS), and Multi-Walled Carbon nanotube (MWCNT) biocomposite films. Abdallh et al 16 improve that the optical band gap and optical activation energy have been investigated for pure and doped PVA films with different cupper chloride concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…These properties make MWCNTs an ideal material for creating an appropriate holding medium for various dopants, as well as for use in energy storage systems. [12][13][14] Researchers have widely utilized multi-walled carbon nanotubes (MWCNTs) owing to their low price, lack of toxicity, and widespread availability. By combining MWCNTs with other transition metal nano-oxides or nano-sulfides, it is possible to create a nanohybrid material with exceptional characteristics and a typically stable structure.…”
mentioning
confidence: 99%
“…By combining MWCNTs with other transition metal nano-oxides or nano-sulfides, it is possible to create a nanohybrid material with exceptional characteristics and a typically stable structure. 15 The impact of multi-walled carbon nanotubes (MWCNTs) on the optical characteristics of polyvinyl alcohol/ chitosan nanocomposites was investigated by Mergen et al 13 for potential use in biological applications. Altalhi et al created blends with polyaniline (PANI), MWCNTs and zinc sulphide (ZnS) nanoparticles for the purpose of using them in biofuel uses.…”
mentioning
confidence: 99%
“…27 Mergen et al investigated the influence of MWCNTs on the optical characteristics of PVA/CS nanocomposites, specifically for bio-applications. 28 Blends created for polyaniline, ZnS and MWCNT nanoparticles were prepared by Altalhi et al 29 for use in biofuel applications. To facilitate rapid charging and discharging, Yin et al 30 created a novel MWCNT-and copper nanowire-based 3D nanocomposite anode.…”
mentioning
confidence: 99%